-6-9x=-5x-4x+7

Simple and best practice solution for -6-9x=-5x-4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-9x=-5x-4x+7 equation:


Simplifying
-6 + -9x = -5x + -4x + 7

Reorder the terms:
-6 + -9x = 7 + -5x + -4x

Combine like terms: -5x + -4x = -9x
-6 + -9x = 7 + -9x

Add '9x' to each side of the equation.
-6 + -9x + 9x = 7 + -9x + 9x

Combine like terms: -9x + 9x = 0
-6 + 0 = 7 + -9x + 9x
-6 = 7 + -9x + 9x

Combine like terms: -9x + 9x = 0
-6 = 7 + 0
-6 = 7

Solving
-6 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10x+25=6x | | -32x+12=-26-32x | | 2q=-6+3q | | -0.5(4+x)=-1.3 | | 10g-9=-9+10g | | 32(1+7x+98)=0 | | 3x-16=21 | | M(m-3)-2m(m-4)=-(m^2-4m) | | 9x+2+5+4=90 | | 5-4k=9-5k | | -20(x+2)+6(4x-6)=3(x-4)+13 | | -8(3n-1)=15n+125 | | 4s=9+4s | | y=35x+15.50 | | 4(-6+m)=4m+10 | | p-0.6=1.8 | | -5p-4=-4-5p | | -38=-8x+2(x-7) | | Z=7+6y | | 3-9+18y=12+24+6y | | 7-5.8z=-23 | | y=-5/7x-6 | | 3/7y-2=7 | | 4-d=2.3d+3 | | 8(2y+5)=12y-(2Y+14) | | -2-10j=-10j-7 | | 4c+22=6 | | 6y+2y=18 | | 3y-2+5y=-18 | | 4x+10=10x-32 | | 6x^2-7-52=0 | | 3x-50=-11 |

Equations solver categories